Spatial Estimations of Suitable Intertidal Habitats for Conservations of Sea Urchin Community in Sancang Coast, West Java - Purwati Kuswarini Suprapto; Ika Raymita Husna; Vita Meylani; Andri Wibowo (Journal of Multidisciplinary Applied Natural Science, 2023)
The intertidal zone is an important habitat for marine organisms, including sea urchins. One of the potential intertidal zones is located on West Java's Sancang Coast. However, information about suitable habitats for sea urchins in this particular intertidal zone is still limited. Here, the spatial estimation of suitable habitats has been implemented aided by scoring, interpolation and overlay analysis of environmental variables and numbers of sea urchin individuals using Geographical Information Systems (GIS). Environmental variable measurements and sea urchin surveys were implemented using the belt transect method. The estimated habitats were located at the Ciporeang, Cikujangjambe and Cibako sites, representing the East, Middle and West sides of intertidal zones that have distinct environmental variables. Based on the results, there were three sea urchin species, with Stomopneustes variolaris having the highest abundance, followed by Heterocentrotus trigonarius, and the lowest one was Diadema setosum. Most species were recorded in Cibako. Correspondingly, the Cibako site has a larger zone classified as very high (70%) and highly suitable (30%) for sea urchins as characterized by seagrass and algae cover, low water temperature, high pH, and salinity parameters. On the contrary, more than 50% of the rocky Ciporeang site zones, with warmer water and low salinity and pH, are not suitable for sea urchins. Therefore, the conservation of the Sancang Coast's sea urchin community should prioritize Cibako sites.